The results of surgical treatment for hepatic hydatid cysts in an endemic area - Bülbüller, Nurullah; Ilhan, Yavuz Selim; Kirkil, Cüneyt; Yeniçerio?lu, Akan; Ayten, Refik; Çetinkaya, Ziya (My University, 2006)
Background/aims: Hydatid cyst remains an important public health problem in endemic areas. Methods: This study retrospectively reviewed medical records of 63 patients treated for hepatic cyst hydatidosis in Firat University, Medical School, Department of General Surgery between January 1994 and December 2002. Results: There were 96 cysts in total in 63 patients, with 67 (69%) of them located in the right lobe of the liver. Of 96 hepatic cysts, 41 (45%) were treated with partial cystectomy and drainage, 25 (26%) with partial cystectomy and capitonnage and 15 (15%) with partial cystectomy and omentoplasty. Thirty-two patients (51%) received treatment with albendazole while 31 (49%) received no medical therapy. The postoperative complication rate was 19% and there was no significant difference in the early post-operative complications between surgical procedures (p>0.05). Cysts recurred in 6 patients (11%) and no correlation was found between recurrence of cysts and albendazole use, type of surgical procedure, number and size of the cysts, Gharbi classification as determined by ultrasound examination or the relation of the cyst with the biliary tract (p>0.05). Conclusion: It was concluded that there was no significant difference in the rates of complications and recurrences among different surgical procedures when performed with basic rules of the surgical principles.
Keywords: Albendazole; Echinococcosis; Hydatid disease